Acute and clinical effects of cryoballoon pulmonary vein isolation in patients with symptomatic paroxysmal and persistent atrial fibrillation - Malmborg, Helena; Lönnerholm, Stefan; Blomström-Lundqvist, Carina (Europace, 2008)
Aims To assess the acute effects, safety, and clinical outcome of atrial fibrillation (AF) ablation using a cryoballoon catheter. Methods and results Forty patients with paroxysmal or persistent AF underwent pulmonary vein (PV) isolation with a cryoballoon catheter (Arctic Front, CryoCath). Electrocardiograms were recorded in case of symptomatic AF recurrences, and a 24 h Holter recording was performed at last follow-up. Complete PV isolation was achieved in 39 (91%) of the 43 procedures (56% with the cryoballoon catheter alone, 44% with an additional conventional ryocatheter). The number of balloon applications per procedure was 9.6 ± 1.6. The PV isolation rate was significantly higher (83.9%) if total vessel occlusions were obtained than if intermediate (63.6%, P = 0.01) or poor occlusions were achieved (38.1%, P = 0.0002). The mean procedure time was 239 ± 48 min. At follow-up (mean 8.9 ± 4.6 months), 52.5% of patients were free from arrhythmia-related symptoms and another 17.5% had reduction of arrhythmia-related symptoms. Two cases each of phrenic nerve paralysis and dysphagia occurred. Conclusions Cryoballoon PV isolation is a feasible technique with a high acute success rate and comparable clinical outcome to radiofrequency ablation. Although complications were rare, the need for an additional conventional cryocatheter warrants further development of the technique.